The Knights of Malta - Sire, H. J. A. (New Haven : Yale University Press, 1994)
The long crusade - The kingdom of Jerusalem - Le Crac des chevaliers - Rhodes - Juan Fernandez de Heredia - The three sieges - Malta - The navy of the relegion - The Order of St John - Provence - Auvergne - Aragon and Castile - Italy, England, Germany - A princely charity - Our Lords the Sick - The closed crown - Ruit alto a Culmune Troia - Resurgence - An intrigue in the Vatican - The modern order - Grand Masters and Lieutenants of the Order of St John - Diplomatic representation of the Order - Institutions of the Order
Includes bibliographical references and index.
Keywords: Knights of Malta -- History; Grand Sovereign Dynastic Hospitaller Order of Saint John -- History